OptoGluNAM4.1, a Photoswitchable Allosteric Antagonist for Real-Time Control of mGlu4 Receptor Activity. Issue 8 (18th August 2016) - Rovira, Xavier; Trapero, Ana; Pittolo, Silvia; Zussy, Charleine; Faucherre, Adèle; Jopling, Chris; Giraldo, Jesús; Pin, Jean-Philippe; Gorostiza, Pau; Goudet, Cyril; Llebaria, Amadeu
Summary: OptoGluNAM4.1, a negative allosteric modulator (NAM) of metabotropic glutamate receptor 4 (mGlu4 ) contains a reactive group that covalently binds to the receptor and a blue-light-activated, fast-relaxing azobenzene group that allows reversible receptor activity photocontrol in vitro and in vivo. OptoGluNAM4.1 induces light-dependent behavior in zebrafish and reverses the activity of the mGlu4 agonist LSP4-2022 in a mice model of chronic pain, defining a photopharmacological tool to better elucidate the physiological roles of the mGlu4 receptor in the nervous system. Graphical Abstract: Highlights: OptoGluNAM4.1 is an azobenzene active as negative allosteric modulator of mGlu4 OptoGluNAM4.1 is isomerized with blue-light/dark cycles with fast relaxation In vivo, OptoGluNAM4.1 regulates the zebrafish embryo motility with light OptoGluNAM4.1 mGlu4 activity is effective in a pain mouse model Abstract : Small molecules with photochromic properties have potential for precise drug therapeutics. Rovira et al. present OptoGluNAM4.1, allowing reversible mGlu4 activity photocontrol in vitro and in vivo that can be used to dissect the physiological roles of this receptor in the nervous system.